Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Ballistic potential of the atlatl and dart for hunting late-Quaternary megafauna - Devin B. Pettigrew; Sam Zhang; Kristen C. Carlson; Robert Hitchcock; Justin Garnett; John C. Whittaker; Carlton Shield Chief Gover; Eric Vance (Quaternary International, 2026)

Dispersion Measurements for Underground Hydrogen Storage over Sequestered CO2 - Sam Kobeissi; Nicholas N. A. Ling; Minzhen Li; Eric F. May; Michael L. Johns (Transport in Porous Media, 2026)
Underground hydrogen storage (UHS) in depleted gas reservoirs is an effective strategy for balancing renewable energy supply and demand, with cushion gases being used to maintain storage pressure. Here CO 2 is investigated as a cushion gas via measurements of the dispersion between hydrogen and CO 2 in a (Bentheimer sandstone) rock core, performed at reservoir-relevant conditions using a novel core flooding apparatus. Such data is required to quantify undesirable mixing between the stored hydrogen and the cushion gas. Dispersion coefficients ( K L ) were measured at 50–100 bar and 22–60 °C, with injection velocities up to 170 m/day, employing benchtop NMR spectroscopy for effluent composition analysis. The value of K L ranged from 0.018 to 0.06 m 2 /day, with most of the measurements performed for H 2 extraction (CO 2 displacing H 2 ). At 22 °C and 50 bar, a representative comparison showed higher dispersion during H 2 injection (H 2 displacing CO 2 ) than during H 2 extraction. This behaviour is attributed to the viscosity ratio (ratio of displaced to displacing fluid) exceeding unity during H 2 injection, promoting viscous fingering. Extrapolation of K L to its value at minimal flow velocity produced a tortuosity value that ranged from 2.24 to 2.63 depending on the diffusion coefficient used, which was consistent with the independent measurement of 2.32 ± 0.20 produced using pulse field gradient (PFG) NMR measurements. Values of the molecular diffusion coefficient ( D 12 ) estimated using Thorne-Enskog theory resulted in the normalised K L / D 12 data collapsing onto a single curve for all of the temperature and pressure conditions considered.

From gels to high-moisture extrudates: pH and 11S:7S globulin ratio govern multiscale structure formation - Ekaterina D. Garina; Sam A. Kuijpers; Martijn I. Gobes; Gregory N. Smith; Michael Sztucki; Arno G.B. Wouters; John P.M. van Duynhoven; Wim G. Bouwman (Food Hydrocolloids, 2026)

FeCl3/KOH two steps activated biocarbon with hierarchical porosity and oxygen-rich for enhanced supercapacitor applications - Amadou Belal Gueye; Sam John; Martin George Thomas; Jephin K. Jose; Modou Fall; Manoj Balachandran; Sabu Thomas (Biomass and Bioenergy, 2026)

Bone Marrow Mesenchymal Stem Cell Extracellular Vesicle Treatment of Respiratory Failure from COVID-19: Endpoint Analysis of Expanded Access Safety Trial - Vikram Sengupta; Sascha Qian; John T. Ransom; Sam Suzuki; David J. Park; Timothy I. Melson; Brian P. Williams; James J. Walsh; Mustafa Awili; Jack M. Mann; Timothy A. Moseley (Stem Cell Reviews and Reports, 2026)

In-Vivo 6D Heart Motion Analysis for Emerging Self-Powered Cardiac Implants - Milad Hasani; John Huber; Benedict Kjærgaard; Tomas Zaremba; Alireza Rezania; Sam Riahi (Annals of Biomedical Engineering, 2026)
Self-powered intracardiac implant devices show great promise for future clinical applications due to their extended operational lifespan and the potential to reduce the need for high-risk repeat surgeries. This study investigates the feasibility of harvesting energy from cardiac motion through in vivo testing of intracardiac devices. Comprehensive three-dimensional translational and rotational cardiac motions are captured in a porcine model using a miniaturized 9-degree-of-freedom motion sensor implanted at six strategic epicardial sites. Kinematic criteria are developed to evaluate the energy harvesting potential of each implant site based on the available kinetic energy, acceleration, and jerk factors. The recorded heart motion signals are analyzed and applied to a conceptual energy harvester proposed to identify the optimal implant site. The results reveal that the left ventricular apex emerges as a preferable site for energy harvesting, particularly at moderate heart rates. These findings offer valuable insights into optimizing self-powered intracardiac implants, reducing dependency on battery replacements, and enhancing long-term patient safety.

Coxiella burnetii shedding in dairy cattle and its correlation with humoral and cell-mediated immune responses - Lucy O’Shannessy; John K. House; Bridgette G. Logan; John M. Morton; Sam Rowe; Paul A. Sheehy; Benjamin U. Bauer; Katrina L. Bosward (Veterinary Microbiology, 2026)

Temporal insights into afforestation: A 25-year study of woodland expansion - Julija Fediajevaite; Aaron Philips; John Tucker; Peter Buckley; Clive Steward; Sam Pettman; John Crawford; Petra Guy; Mark Tibbett; Nadia Barsoum; Brian J. Pickles (Forest Ecology and Management, 2026)

EveryOne, EveryWhere, EveryWhen: Just water futures for three Living Rivers - R. Quentin Grafton; Anne Poelina; William Brian (Badger) Bates; Matthew Currell; David Doyle; Kirsty Howey; Cecilia Lake; Caroline McFarlane; Anthony McLarty; Nhat-Mai Nguyen; Sam Phelan; Patricia Riley; et al. (Water Security, 2026)

Genomic analysis of a porcine exudative epidermitis outbreak caused by Staphylococcus hyicus - Alec Truswell; David Jordan; Stanley Pang; Tanya Cherrington; David J. Hampson; John Blinco; Sandy Adsett; Rebecca Abraham; Marc Stegger; Sam Abraham (Veterinary Microbiology, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Mapping anisotropic structure formation of soy protein during high-moisture extrusion - Ekaterina D. Garina; Sam A. Kuijpers; Martijn I. Gobes; Arjen Sein; Ruud den Adel; Gregory N. Smith; Michael Sztucki; Johannes Hohlbein; Camilla Terenzi; John P.M. van Duynhoven; Wim G. Bouwman (Food Hydrocolloids, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Gaps in tipping points research across freshwater, marine, and terrestrial ecosystems - Meagan Harper; Charlotte Carrier-Belleau; Trina Rytwinski; Brian Helmuth; Irena F. Creed; John P. Smol; Joseph R. Bennett; Dalal E.L. Hanna; Leonardo A. Saravia; Juan Rocha; Aubrey Foulk; Sam Dupont; et al. (Biological Conservation, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Impact of pH-shifting on multiscale structural anisotropy of high-moisture extrudates of soy proteins - Sam A. Kuijpers; Ekaterina D. Garina; Martijn I. Gobes; Ruud den Adel; Gregory N. Smith; Michael Sztucki; Johannes Hohlbein; Wim G. Bouwman; John P.M. van Duynhoven; Camilla Terenzi (Food Hydrocolloids, 2025)

Bighorn sheep respond to mountain lions with temporally dynamic forage-risk tradeoffs - Kate A. Asmus; Gavin G. Cotterill; Todd D. Nordeen; Sam Wilson; Peter J. Mahoney; John F. Benson (Biological Conservation, 2025)

Small fish, big implications: considerations for an ecosystem approach to capelin fisheries management - Warsha Singh; John T. Trochta; Hannah M. Murphy; David W. McGowan; Aaron T. Adamack; Mayumi L. Arimitsu; Birkir Barðarson; Höskuldur Björnsson; Bjarte Bogstad; Mathieu Boudreau; Catherine Chambers; Harald Gjøsæter; et al. (Reviews in Fish Biology and Fisheries, 2025)

Are Ecotonal Systems More Sensitive to Climate Change? Past Ecotonal Dynamics and Rates of Vegetation Change in Michigan - Sam Wiles; Nora Schlenker; David M. Nelson; Bryan Shuman; John W. Williams (Global Ecology and Biogeography, 2025)
Aim Ecotones are expected to be sensitive to climate change, but supporting evidence is scarce. Here we test the ecotonal sensitivity hypothesis by reconstructing past movements of a major temperature‐governed forest ecotone (the Tension Zone, separating temperate deciduous forests and northern mixed hardwood‐conifer forests) and comparing the variability of ecotone‐proximal and distal vegetation. Location Michigan, United States. Time Period Holocene. Major Taxa Studied Temperate tree taxa in north‐central U.S. Methods We apply non‐metric multidimensional scaling (NMDS) and empirical Bayesian Kriging (EBK) to a new pollen record from Sunrise Lake, MI located in the Tension Zone and 19 extant fossil pollen datasets from the Neotoma Paleoecology Database to track movements of the Tension Zone during the Holocene and use the R‐Ratepol package to measure compositional variability. Results NMDS Axis 2 clusters southern hardwoods from northern mixed forest, and so can be used to indicate Tension Zone position, while Axis 4 captures shifts in mesic versus xeric taxa, Axis 1 captures the early Holocene decline of Picea woodlands and Axis 3 captures the rise of Ambrosia ‐dominated assemblages after Euro‐American settlement. At Sunrise Lake, which is within the Tension Zone, major changes include expansions of Tsuga canadensis populations at 6.7 ka and Fagus grandifolia at 6.3 ka BP. The Tension Zone shifted northwards by approximately 150 km from 11 and 6 ka during a 3.5°C TJuly warming, then retreated southwards, reaching its current position by 2 ka. Sites close to the Tension Zone ecotone show more compositional variability than distal sites, suggesting that ecotonal populations in Michigan were more sensitive to Holocene climate variability. This relationship varied over time and strengthened after 6 ka. Main Conclusions These findings support the ecotonal sensitivity hypothesis, constrain estimates of climate‐driven forest ecotonal movement, and reinforce concerns about the sensitivity of ecotonal ecosystems to anthropogenic global warming.

The value of a structured, systematic approach to benefit-risk assessment of medicines: A South African regulator case study - Lorraine Danks; Boitumelo Semete-Makokotlela; Donald Chuma; John-Joseph Borg; Star Khoza; Stuart Walker; Sam Salek (Regulatory Toxicology and Pharmacology, 2025)

Effect of supplemental diets based on Ficusnatalensis and Harrisoniaabyssinica on the meat quality of tethered indigenous goat meat - Dorothy Kalule Nampanzira; Justus Kwetegyeka; Kamatara Kanifa; Denis Asizua; Christine Kyarimpa; Muhammad Kiggundu; Constantine Bakyusa Katongole; John David Kabasa; Sam Okello; John Robert Stephen Tabuti (Agroforestry Systems, 2025)

Farmer uptake of cassava-whitefly management technologies and implications for future breeding and promotional efforts - Irene Bayiyana; Anton Bua; Annet Namuddu; Alfred Ozimati; Tom Omara; Sam Wamani; Sam Morris Opio; Sarah Apio; Richard Kabaalu; Daisy Kemigisha; John Colvin; Christopher Abu Omongo (Crop Protection, 2025)

Spatial ecology of recolonized elk in agricultural landscapes of the Northern Great Plains - Tabitha A. Hughes; Todd Nordeen; Luke Meduna; Sam P. Wilson; John F. Benson (Biological Conservation, 2025)

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Superstep wavefield propagation - Tamas Nemeth; Kurt Nihei; Alex Loddoch; Anusha Sekar; Ken Bube; John Washbourne; Luke Decker; Sam Kaplan; Chunling Wu; Andrey Shabelansky; Milad Bader; Ovidiu Cristea; et al. (Wave Motion, 2025)

Rotated Fourier transform (RFT) enables the quantification of anisotropic structure in high-moisture plant-protein extrudates - Martijn I. Gobes; Sam A. Kuijpers; Camilla Terenzi; Ruud G.M. van der Sman; John P.M. van Duynhoven; Johannes Hohlbein (Food Structure, 2025)

Australian subtropical vegetation and wetland response to fire, climate and nutrient availability during the Holocene - Haidee Cadd; Michela Mariani; John Tibby; Jonathan Tyler; Cameron Barr; Melanie J. Leng; Patrick Moss; Richard Lewis; Tim Cohen; Sam Marx; Glenn B. McGregor; Jonathan C. Marshall; et al. (Journal of Quaternary Science, 2025)
The iconic sand dune systems of Minjerribah (North Stradbroke Island), in southeastern Queensland, Australia, host numerous lakes and swamps containing organic‐rich sediment deposits that record changes in climate, fire and surrounding vegetation. Palaeoenvironmental reconstructions from individual locations can provide insights into changes in the environment, but determining the regional extent of these changes is seldom possible from a single site. Multi‐site compilations help elucidate the geographical nature of environmental changes and determine if they are driven by local or regional forces. Here, a synthesis of palynological records from six Minjerribah wetlands using a muti‐tiered Monte Carlo empirical orthogonal function (EOF) analysis allows island‐wide patterns of vegetation change to be identified. Coherent changes in vegetation were recorded, with first‐order changes (EOF1) indicating a long‐term shift in vegetation composition from closed forests towards woodland and heath vegetation. A compilation of macroscopic and microscopic charcoal from the same sites shares coherent patterns of change with a rainfall record from the island, suggesting that regional fire occurrence between 7000 and 2000 cal a bp was driven primarily by long‐term variations in rainfall and its influence on biomass. Comparison with fire activity, rainfall, sedimentary carbon, nitrogen and dust records from Minjerribah suggests that regional vegetation changes occur primarily in response to long‐term changes in nutrients and increasing rainfall variability. This analysis highlights the multi‐millennial connection between vegetation composition, climate, nutrients and fire occurrence across the Holocene in subtropical environments.

Differences in the Prevalence of Sleep-Related Disorders Among Normal, Overweight and Obese Adolescents - George Varghese Mani; Praveen George Paul; Anish Sam George; Shincy Tomy John; Jansi Rani; Mona M. Basker; Sneha Varkki (Sleep and Vigilance, 2025)

Effects of fine-scale changes in resource access and social stability on the sociality of foraging flocks of wild birds - Camille A. Troisi; Josh A. Firth; Sam J. Crofts; Gabrielle L. Davidson; Michael S. Reichert; John L. Quinn (Animal Behaviour, 2025)

Quantification of phase separation in high moisture soy protein extrudates by NMR and MRI - Sam A. Kuijpers; Gert-Jan Goudappel; Thom Huppertz; John P.M. van Duynhoven; Camilla Terenzi (Food Research International, 2024)

A comprehensive review of 5G NR RF-EMF exposure assessment technologies: fundamentals, advancements, challenges, niches, and implications - Erdal Korkmaz; Sam Aerts; Richard Coesoij; Chhavi Raj Bhatt; Maarten Velghe; Loek Colussi; Derek Land; Nikolaos Petroulakis; Marco Spirito; John Bolte (Environmental Research, 2024)

Reduction of large vessel traffic improves water quality and alters fish habitat-use throughout a large river - Michael J. Spear; Brandon S. Harris; Taylor A. Bookout; Brian S. Ickes; Kathi Jo Jankowski; Levi E. Solomon; Kristopher A. Maxson; Andrya L. Whitten Harris; Andrew T. Mathis; Sam J. Schaick; Jesse A. Williams; Jason A. DeBoer; et al. (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

A new species of Choleoeimeria (Apicomplexa: Eimeriidae) from the invasive curious skink, Carlia ailanpalai (Sauria: Scincidae) from Guam, U.S. Territory - Chris T. McAllister; John A. Hnida; Diane Vice; Sam R. Fisher; Robert N. Fisher (Systematic Parasitology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Twenty‐five emerging questions when detecting, understanding, and predicting future fish distributions in a changing climate - Molly M. Kressler; Georgina L. Hunt; Anna K. Stroh; John K. Pinnegar; Jonathan Mcdowell; Joseph W. Watson; Marcelo P. Gomes; Michał E. Skóra; Sam Fenton; Richard D. M. Nash; Rui Vieira; Martha Patricia Rincón‐Díaz (Journal of Fish Biology, 2024)
The 2023 Annual Symposium of the Fisheries Society of the British Isles hosted opportunities for researchers, scientists, and policy makers to reflect on the state of art of predicting fish distributions and consider the implications to the marine and aquatic environments of a changing climate. The outcome of one special interest group at the Symposium was a collection of questions, organized under five themes, which begin to capture the state of the field and identify priorities for research and management over the coming years. The five themes were Physiology, Mechanisms, Detect and Measure, Manage, and Wider Ecosystems. The questions, 25 of them, addressed concepts which remain poorly understood, are data deficient, and/or are likely to be impacted in measurable or profound ways by climate change. Moving from the first to the last theme, the questions expanded in the scope of their considerations, from specific processes within the individual to ecosystem‐wide impacts, but no one question is bigger than any other: each is important in detecting, understanding, and predicting fish distributions, and each will be impacted by an aspect of climate change. In this way, our questions, particularly those concerning unknown mechanisms and data deficiencies, aimed to offer a guide to other researchers, managers, and policy makers in the prioritization of future work as a changing climate is expected to have complex and disperse impacts on fish populations and distributions that will require a coordinated effort to address.

Conducting volcanic ash cloud exercises: practising forecast evaluation procedures and the pull-through of scientific advice to the London VAAC - Frances Beckett; Sara Barsotti; Ralph Burton; Fabio Dioguardi; Sam Engwell; Matthew Hort; Nina Kristiansen; Sue Loughlin; Anton Muscat; Martin Osborne; Cameron Saint; John Stevenson; et al. (Bulletin of Volcanology, 2024)
The London Volcanic Ash Advisory Centre (VAAC) provides forecasts on the expected presence of volcanic ash in the atmosphere to mitigate the risk to aviation. It is fundamentally important that operational capability is regularly tested through exercises, to guarantee an effective response to an event. We have developed exercises which practise the pull-through of scientific advice into the London VAAC, the forecast evaluation process, and the decision-making procedures and discussions needed for generating the best possible forecasts under real-time conditions. London VAAC dispersion model forecasts are evaluated against observations. To test this capability in an exercise, we must create observation data for a hypothetical event. We have developed new methodologies for generating and using simulated satellite and lidar retrievals. These simulated observations enable us to practise our ability to interpret, compare, and evaluate model output and observation data under real-time conditions. Forecast evaluation can benefit from an understanding of how different choices of model setup (input parameters), model physics, and driving meteorological data impact the predicted extent and concentration of ash. Through our exercises, we have practised comparing output from model simulations generated using different models, model setups, and meteorological data, supplied by different institutions. Our exercises also practise the communication and interaction between Met Office (UK) scientists supporting the London VAAC and external experts, enabling knowledge exchange and discussions on the interpretation of model output and observations, as we strive to deliver the best response capability for the aviation industry and stakeholders. In this paper, we outline our exercise methodology, including the use of simulated satellite and lidar observations, and the development of the strategy to compare output generated from different modelling systems. We outline the lessons learnt, including the benefits and challenges of conducting exercises which practise our ability to provide scientific advice for an operational response at the London VAAC.

Biocontrol efficiency of Trichoderma asperellum in managing branch canker disease of tea (Camelia sp.), its effect on vegetative growth, natural enemies and phytotoxicity - Kishor Chand Kumhar; Azariah Babu; John Peter Arulmarianathan; Bhabesh Deka; Mitali Bordoloi; Hirakjyoti Rajbongshi; Pritam Dey; Sam Nirmala Nisha (Indian Phytopathology, 2024)

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

ACPSEM position paper: pre-treatment patient specific plan checks and quality assurance in radiation oncology - Lotte S. Fog; Luke K. Webb; Jeffrey Barber; Matthew Jennings; Sam Towns; Susana Olivera; John Shakeshaft (Physical and Engineering Sciences in Medicine, 2024)

Corrigendum to “Compositional and metabolic responses of European seabass (Dicentrarchus labrax) to a dietary gradient of long-chain (≥ C20) polyunsaturated fatty acids” [Aquaculture 580 (2024) 740304] - Sam J.S. Houston; Vasileios Karalazos; John Tinsley; Douglas R. Tocher; Óscar Monroig (Aquaculture, 2024)

Compositional and metabolic responses of European seabass (Dicentrarchus labrax) to a dietary gradient of long-chain (≥ C20) polyunsaturated fatty acids - Sam J.S. Houston; Vasileios Karalazos; John Tinsley; Douglas R. Tocher; Óscar Monroig (Aquaculture, 2024)

A soil spectral library of New Zealand - Yuxin Ma; Pierre Roudier; Kishor Kumar; Thilak Palmada; Gerard Grealish; Sam Carrick; Linda Lilburne; John Triantafilis (Geoderma Regional, 2023)

Topological Data Analysis Captures Task-Driven fMRI Profiles in Individual Participants: A Classification Pipeline Based on Persistence - Michael J. Catanzaro; Sam Rizzo; John Kopchick; Asadur Chowdury; David R. Rosenberg; Peter Bubenik; Vaibhav A. Diwadkar (Neuroinformatics, 2023)

Nerine potexvirus 1: a new Potexvirus species detected from Nerine in the United Kingdom - Naomi Beddoe; Sam McGreig; John Walsh; Adrian Fox; Ian P. Adams; Alec Forsyth (Journal of Plant Pathology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Identification and characterization of Phaseolus vulgaris endornavirus 1, 2 and 3 in common bean cultivars of East Africa - Thomas J. Brine; Sam Crawshaw; Alex M. Murphy; Adrienne E. Pate; John P. Carr; Francis O. Wamonje (Virus Genes, 2023)
Persistent viruses include members of the family Endornavirus that cause no apparent disease and are transmitted exclusively via seed or pollen. It is speculated that these RNA viruses may be mutualists that enhance plant resilience to biotic and abiotic stresses. Using reverse transcription coupled polymerase chain reactions, we investigated if common bean ( Phaseolus vulgaris L.) varieties popular in east Africa were hosts for Phaseolus vulgaris endornavirus (PvEV) 1, 2 or 3. Out of 26 bean varieties examined, four were infected with PvEV1, three were infected with both PvEV1 and PvEV2 and three had infections of all three (PvEV) 1, 2 and 3. Notably, this was the first identification of PvEV3 in common bean from Africa. Using high-throughput sequencing of two east African bean varieties (KK022 and KK072), we confirmed the presence of these viruses and generated their genomes. Intra- and inter-species sequence comparisons of these genomes with comparator sequences from GenBank revealed clear species demarcation. In addition, phylogenetic analyses based on sequences generated from the helicase domains showed that geographical distribution does not correlate to genetic relatedness or the occurrence of endornaviruses. These findings are an important first step towards future investigations to determine if these viruses engender positive effects in common bean, a vital crop in east Africa.

A DNA-barcode biodiversity standard analysis method (DNA-BSAM) reveals a large variance in the effect of a range of biological, chemical and physical soil management interventions at different sites, but location is one of the most important aspects determining the nature of agricultural soil microbiology - Matías Fernández-Huarte; John G. Elphinstone; Ian P. Adams; Joana G. Vicente; Anne Bhogal; Christine A. Watson; Francois Dussart; Elizabeth A. Stockdale; John Walshaw; Sam McGreig; Robert W. Simmons; Lucie Mašková; et al. (Soil Biology and Biochemistry, 2023)

Molecular characterisation of the Australian and New Zealand livestock Chlamydia pecorum strains confirms novel but clonal ST23 in association with ovine foetal loss - Martina Jelocnik; Rhys T. White; Tom Clune; John O’Connell; Jonathan Foxwell; Sam Hair; Shane Besier; La Tom; Nyree Phillips; Amy Robbins; Daniel Bogema; Paola K. Vaz; et al. (Veterinary Microbiology, 2023)

Comparative analysis of UK net-zero scenarios: The role of energy demand reduction - Elliott Johnson; Sam Betts-Davies; John Barrett (Energy Policy, 2023)

Impact of sea ice transport on Beaufort Gyre liquid freshwater content - Sam B. Cornish; Morven Muilwijk; Jeffery R. Scott; Juliana M. Marson; Paul G. Myers; Wenhao Zhang; Qiang Wang; Yavor Kostov; Helen L. Johnson; John Marshall (Climate Dynamics, 2023)
The Arctic Ocean’s Beaufort Gyre (BG) is a wind-driven reservoir of relatively fresh seawater, situated beneath time-mean anticyclonic atmospheric circulation, and is covered by mobile pack ice for most of the year. Liquid freshwater accumulation in and expulsion from this gyre is of critical interest due to its potential to affect the Atlantic meridional overturning circulation and due to the importance of freshwater in modulating vertical fluxes of heat, nutrients and carbon in the ocean, and exchanges of heat and moisture with the atmosphere. Here, we investigate the hypothesis that wind-driven sea ice transport into/from the BG region influences the freshwater content of the gyre and its variability. To test this hypothesis, we use the results of a coordinated climate response function experiment with four ice-ocean models, in combination with targeted experiments using a regional setup of the MITgcm, in which we rotate the surface wind forcing vectors (thereby changing the ageostrophic component of these winds). Our results show that, via an effect on the net thermodynamic growth rate, anomalies in sea ice transport into the BG affect liquid freshwater adjustment. Specifically, increased ice import increases freshwater retention in the gyre, whereas ice export decreases freshwater in the gyre. Our results demonstrate that uncertainty in the ageostrophic component of surface winds, and in the dynamic sea ice response to these winds, has important implications for ice thermodynamics and freshwater. This sensitivity may explain some of the observed inter-model spread in simulations of Beaufort Gyre freshwater and its adjustment in response to wind forcing.

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

Cognitive performance in a South African cohort of people with HIV and comorbid major depressive disorder - Anna J. Dreyer; Sam Nightingale; Lena S. Andersen; Jasper S. Lee; Hetta Gouse; Steven A. Safren; Conall O’Cleirigh; Kevin G. F. Thomas; John Joska (Journal of NeuroVirology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Dead-infant carrying by chimpanzee mothers in the Budongo Forest - Adrian Soldati; Pawel Fedurek; Catherine Crockford; Sam Adue; John Walter Akankwasa; Caroline Asiimwe; Jackson Asua; Gideon Atayo; Boscou Chandia; Elodie Freymann; Caroline Fryns; Geresomu Muhumuza; et al. (Primates, 2022)
It has been suggested that non-human primates can respond to deceased conspecifics in ways that suggest they experience psychological states not unlike humans, some of which could indicate they exhibit a notion of death. Here, we report long-term demographic data from two East African chimpanzee groups. During a combined 40-year observation period, we recorded 191 births of which 68 died in infancy, mostly within the first year. We documented the post-mortem behaviour of the mothers and describe nine occasions where Budongo chimpanzee mothers carried infants for 1–3 days after their death, usually until the body started to decompose. We also observed three additional cases of extended carrying lasting for more than 2 weeks, one of which was followed by the unusual extended carrying of an object and another which lasted 3 months. In each case, the corpses mummified. In addition, we report four instances of recurring dead-infant carrying by mothers, three of whom carried the corpse for longer during the second instance. We discuss these observations in view of functional hypotheses of dead-infant carrying in primates and the potential proximate mechanisms involved in this behaviour.

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - S. James Reynolds; Colin P. Wearn; B. John Hughes; Roger C. Dickey; Lucy J. H. Garrett; Sean Walls; Fay T. Hughes; Nicola Weber; Sam B. Weber; Eliza H. K. Leat; Kenickie Andrews; Jaime A. Ramos; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns ( Onychoprion fuscatus ) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.

Rates of cognitive impairment in a South African cohort of people with HIV: variation by definitional criteria and lack of association with neuroimaging biomarkers - Anna J. Dreyer; Sam Nightingale; Jodi M. Heaps-Woodruff; Michelle Henry; Hetta Gouse; Robert H. Paul; Kevin G. F. Thomas; John A. Joska (Journal of NeuroVirology, 2021)

Neolithic farmers or Neolithic foragers? Organic residue analysis of early pottery from Rakushechny Yar on the Lower Don (Russia) - Manon Bondetti; Lara González Carretero; Ekaterina Dolbunova; Krista McGrath; Sam Presslee; Alexandre Lucquin; Viktor Tsybriy; Andrey Mazurkevich; Andrey Tsybriy; Peter Jordan; Carl Heron; John Meadows; et al. (Archaeological and Anthropological Sciences, 2021)
The emergence of pottery in Europe is associated with two distinct traditions: hunter-gatherers in the east of the continent during the early 6th millennium BC and early agricultural communities in the south-west in the late 7th millennium BC. Here we investigate the function of pottery from the site of Rakushechny Yar, located at the Southern fringe of Eastern Europe, in this putative contact zone between these two economic ‘worlds’. To investigate, organic residue analysis was conducted on 120 samples from the Early Neolithic phase (ca. mid-6 th millennium BC) along with microscopic and SEM analysis of associated foodcrusts. The results showed that the earliest phase of pottery use was predominantly used to process riverine resources. Many of the vessels have molecular and isotopic characteristics consistent with migratory fish, such as sturgeon, confirmed by the identification of sturgeon bony structures embedded in the charred surface deposits. There was no evidence of dairy products in any of the vessels, despite the fact these have been routinely identified in coeval sites to the south. Further analysis of some of the mammalian bones using ZooMS failed to demonstrate that domesticated animals were present in the Early Neolithic. Nevertheless, we argue that intensive exploitation of seasonally migratory fish, accompanied by large-scale pottery production, created storable surpluses that led to similar socio-economic outcomes as documented in early agricultural societies.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Synthesis of Thresholds of Ocean Acidification Impacts on Echinoderms - Nina Bednaršek; Piero Calosi; Richard A. Feely; Richard Ambrose; Maria Byrne; Kit Yu Karen Chan; Sam Dupont; Jacqueline L. Padilla-Gamiño; John I. Spicer; Faycal Kessouri; Miranda Roethler; Martha Sutula; et al. (Frontiers in Marine Science, 2021)
Assessing the vulnerability of marine invertebrates to ocean acidification (OA) requires an understanding of critical thresholds at which developmental, physiological, and behavioral traits are affected. To identify relevant thresholds for echinoderms, we undertook a three-step data synthesis, focused on California Current Ecosystem (CCE) species. First, literature characterizing echinoderm responses to OA was compiled, creating a dataset comprised of >12,000 datapoints from 41 studies. Analysis of this data set demonstrated responses related to physiology, behavior, growth and development, and increased mortality in the larval and adult stages to low pH exposure. Second, statistical analyses were conducted on selected pathways to identify OA thresholds specific to duration, taxa, and depth-related life stage. Exposure to reduced pH led to impaired responses across a range of physiology, behavior, growth and development, and mortality endpoints for both larval and adult stages. Third, through discussions and synthesis, the expert panel identified a set of eight duration-dependent, life stage, and habitat-dependent pH thresholds and assigned each a confidence score based on quantity and agreement of evidence. The thresholds for these effects ranged within pH from 7.20 to 7.74 and duration from 7 to 30 days, all of which were characterized with either medium or low confidence. These thresholds yielded a risk range from early warning to lethal impacts, providing the foundation for consistent interpretation of OA monitoring data or numerical ocean model simulations to support climate change marine vulnerability assessments and evaluation of ocean management strategies. As a demonstration, two echinoderm thresholds were applied to simulations of a CCE numerical model to visualize the effects of current state of pH conditions on potential habitat.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Investing in Blue Natural Capital to Secure a Future for the Red Sea Ecosystems - Maha J. Cziesielski; Carlos M. Duarte; Nojood Aalismail; Yousef Al-Hafedh; Andrea Anton; Faiyah Baalkhuyur; Andrew C. Baker; Thorsten Balke; Iliana B. Baums; Michael Berumen; Vasiliki I. Chalastani; Brendan Cornwell; et al. (Frontiers in Marine Science, 2021)
For millennia, coastal and marine ecosystems have adapted and flourished in the Red Sea’s unique environment. Surrounded by deserts on all sides, the Red Sea is subjected to high dust inputs and receives very little freshwater input, and so harbors a high salinity. Coral reefs, seagrass meadows, and mangroves flourish in this environment and provide socio-economic and environmental benefits to the bordering coastlines and countries. Interestingly, while coral reef ecosystems are currently experiencing rapid decline on a global scale, those in the Red Sea appear to be in relatively better shape. That said, they are certainly not immune to the stressors that cause degradation, such as increasing ocean temperature, acidification and pollution. In many regions, ecosystems are already severely deteriorating and are further threatened by increasing population pressure and large coastal development projects. Degradation of these marine habitats will lead to environmental costs, as well as significant economic losses. Therefore, it will result in a missed opportunity for the bordering countries to develop a sustainable blue economy and integrate innovative nature-based solutions. Recognizing that securing the Red Sea ecosystems’ future must occur in synergy with continued social and economic growth, we developed an action plan for the conservation, restoration, and growth of marine environments of the Red Sea. We then investigated the level of resources for financial and economic investment that may incentivize these activities. This study presents a set of commercially viable financial investment strategies, ecological innovations, and sustainable development opportunities, which can, if implemented strategically, help ensure long-term economic benefits while promoting environmental conservation. We make a case for investing in blue natural capital and propose a strategic development model that relies on maintaining the health of natural ecosystems to safeguard the Red Sea’s sustainable development.

A new acroeimerian (Apicomplexa: Eimeriidae) in spotted house gecko, Gekko monarchus (Schlegel) (Sauria: Gekkonidae) from Peninsular Malaysia - Chris T. McAllister; John A. Hnida; Sam R. Fisher; L. A. Del Pinto; Evan S. H. Quah (Systematic Parasitology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Lessons from the past, policies for the future: resilience and sustainability in past crises - John Haldon; Merle Eisenberg; Lee Mordechai; Adam Izdebski; Sam White (Environment Systems and Decisions, 2020)

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Comparative toxicoproteogenomics of mouse and rat liver identifies TCDD-resistance genes - Stephenie D. Prokopec; Aileen Lu; Sandy Che-Eun S. Lee; Cindy Q. Yao; Ren X. Sun; John D. Watson; Rabah Soliymani; Richard de Borja; Ada Wong; Michelle Sam; Philip Zuzarte; John D. McPherson; et al. (Archives of Toxicology, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic? - S. James Reynolds; B. John Hughes; Colin P. Wearn; Roger C. Dickey; Judith Brown; Nicola L. Weber; Sam B. Weber; Vitor H. Paiva; Jaime A. Ramos (Global Change Biology, 2019)
In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns ( Onychoprion fuscatus ) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift occurred during the second half of the twentieth century coinciding with an apparent population collapse of approximately 84%. After correcting for the “Suess Effect,” δ 13 C in feathers declined by ~1.5‰ and δ 15 N by ~2‰ between the 1890s and the present day, indicating that birds changed their diets markedly over the period of population decline. Isotopic niches were equally wide before and after the population collapse but isotopic mixing models suggest that birds have grown ever more reliant on nutrient‐poor squid and invertebrates as teleost fish have declined in availability. Given that sooty terns rely heavily on associations with sub‐surface predators such as tuna to catch fish prey, the rapid expansion of industrialized fisheries for these species over the same period seems a plausible mechanism. Our results suggest that changes to marine ecosystems over the past 60 years have had a dramatic impact on the ecology of the most abundant seabird of tropical oceans, and highlight the potentially pervasive consequences of large predatory fish depletion on marine ecosystem function.

Propagation of future climate conditions into hydrologic response from coastal southern California watersheds - Dongmei Feng; Edward Beighley; Roozbeh Raoufi; John Melack; Yuanhao Zhao; Sam Iacobellis; Daniel Cayan (Climatic Change, 2019)

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

Bioaccumulation factors and multivariate analysis of heavy metals of three edible fish species from the Barekese reservoir in Kumasi, Ghana - Eric Gyimah; Osei Akoto; John Kenneth Mensah; Nesta Bortey-Sam (Environmental Monitoring and Assessment, 2018)

Population collapse dynamics in Acropora downingi , an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature - Bernhard Riegl; Matthew Johnston; Sam Purkis; Emily Howells; John Burt; Sascha C. C. Steiner; Charles R. C. Sheppard; Andrew Bauman (Global Change Biology, 2018)
As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave‐exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table‐coral species A. downingi , population dynamics corresponding to disturbance regimes was quantified in three transition matrices (lower disturbance pre‐1996; moderate disturbance from 1998 to 2010 and 2013 to 2017, disturbed in 1996/1998, 2010/11/12, 2017). Increased disturbance frequency and severity caused progressive reduction in coral size, cover, and population fecundity. Small size‐classes were bolstered more by partial colony mortality than sexual recruitment. Some large corals had a size refuge and resisted die‐back but were also lost with increasing disturbance. Matrix and biophysical larval flow models suggested one metapopulation. Southern, Arabian, populations could be connected to northern, Iranian, populations but this connectivity was lost under assumptions of pelagic larval duration at rising temperatures shortened to a third. Then, the metapopulation disintegrated into isolated populations. Connectivity required to avoid extinctions increased exponentially with disturbance frequency and correlation of disturbances across the metapopulation. Populations became unsustainable at eight disturbances in 15 years, when even highest theoretical recruitment no longer compensated mortality. This lethal disturbance frequency was 3‐fold that of the moderately disturbed monitoring period and 4‐fold of the preceding low‐disturbance period—suggesting ongoing shortening of the disturbance‐free period. Observed population collapse and environmental changes in the Gulf suggest that A. downingi is heading toward at least functional extinction mainly due to increasingly frequent temperature‐induced mortality events, clearly linked to climate change.

Sediment Metal Contamination in the Kafue River of Zambia and Ecological Risk Assessment - Ethel M’kandawire; Kennedy Choongo; John Yabe; Maxwell Mwase; Ngonda Saasa; Shouta M. M. Nakayama; Nesta Bortey-Sam; Claudia A. Blindauer (Bulletin of Environmental Contamination and Toxicology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Repeat photography confirms alarming decline in South African cycads - Desale Y. Okubamichael; Sam Jack; J. De Wet Bösenberg; M. Timm Hoffman; John S. Donaldson (Biodiversity and Conservation, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Midpoint attractors and species richness: Modelling the interaction between environmental drivers and geometric constraints - Robert K. Colwell; Nicholas J. Gotelli; Louise A. Ashton; Jan Beck; Gunnar Brehm; Tom M. Fayle; Konrad Fiedler; Matthew L. Forister; Michael Kessler; Roger L. Kitching; Petr Klimes; Jürgen Kluge; et al. (Ecology Letters, 2016)
We introduce a novel framework for conceptualising, quantifying and unifying discordant patterns of species richness along geographical gradients. While not itself explicitly mechanistic, this approach offers a path towards understanding mechanisms. In this study, we focused on the diverse patterns of species richness on mountainsides. We conjectured that elevational range midpoints of species may be drawn towards a single midpoint attractor – a unimodal gradient of environmental favourability. The midpoint attractor interacts with geometric constraints imposed by sea level and the mountaintop to produce taxon‐specific patterns of species richness. We developed a Bayesian simulation model to estimate the location and strength of the midpoint attractor from species occurrence data sampled along mountainsides. We also constructed midpoint predictor models to test whether environmental variables could directly account for the observed patterns of species range midpoints. We challenged these models with 16 elevational data sets, comprising 4500 species of insects, vertebrates and plants. The midpoint predictor models generally failed to predict the pattern of species midpoints. In contrast, the midpoint attractor model closely reproduced empirical spatial patterns of species richness and range midpoints. Gradients of environmental favourability, subject to geometric constraints, may parsimoniously account for elevational and other patterns of species richness.

Where are the gaps in climate finance? - Sam Fankhauser; Aditi Sahni; Annie Savvas; John Ward (Climate and Development, 2016)

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

Assessing multi-taxa sensitivity to the human footprint, habitat fragmentation and loss by exploring alternative scenarios of dispersal ability and population size: a simulation approach - Brian K. Hand; Sam A. Cushman; Erin L. Landguth; John Lucotch (Biodiversity and Conservation, 2014)

The effects of land use changes on streams and rivers in mediterranean climates - Scott D. Cooper; P. Sam Lake; Sergi Sabater; John M. Melack; John L. Sabo (Hydrobiologia, 2013)

The perfect neuroimaging-genetics-computation storm: collision of petabytes of data, millions of hardware devices and thousands of software tools - Ivo D. Dinov; Petros Petrosyan; Zhizhong Liu; Paul Eggert; Alen Zamanyan; Federica Torri; Fabio Macciardi; Sam Hobel; Seok Woo Moon; Young Hee Sung; Zhiguo Jiang; Jennifer Labus; et al. (Brain Imaging and Behavior, 2013)

The ice age ecologist: testing methods for reserve prioritization during the last global warming - John W. Williams; Heather M. Kharouba; Sam Veloz; Mark Vellend; Jason McLachlan; Zhengyu Liu; Bette Otto‐Bliesner; Feng He (Global Ecology and Biogeography, 2013)
Aim We play the role of an ice age ecologist (IAE) charged with conserving biodiversity during the climate changes accompanying the last deglaciation. We develop reserve‐selection strategies for the IAE and check them against rankings based on modern data. Location Northern and eastern North America. Methods Three reserve‐selection strategies are developed. (1) Abiotic: the IAE uses no information about species–climate relationships, instead maximizing the climatic and geographic dispersion of reserves. (2) Species distribution models (SDMs): the IAE uses boosted‐regression trees calibrated against pollen data and CCSM3 palaeoclimatic simulations from 21 to 15 ka bp to predict modern taxon distributions, then uses these as input to the Z onation reserve‐ranking program. (3) Rank‐and‐regress: regression models are used to identify climatic predictors of zonation rankings. All strategies are assessed against a Z onation ranking based on modern pollen distributions. Analysis units are ecoregions and grid cells. Results The abiotic strategy has a negative or no correlation between predicted and actual rankings. The SDM‐based strategy fares better, with a significantly positive area‐corrected correlation ( r = 0.474, P 0.001) between predicted and actual rankings. Predictive ability drops when grid cells are the analysis unit ( r = 0.217, P = 0.058). Predictive ability for the rank‐and‐regress strategy is similar to the SDM results. Main conclusions For the IAE, SDMs improve the predictive ability of reserve‐selection strategies. However, predictive ability is limited overall, probably due to shifted realized niches during past no‐analogue climates, new species interactions as species responded individually to climate change, and other environmental changes not included in the model. Twenty‐first‐century conservation planning also faces these challenges, and is further complicated by other anthropogenic impacts. The IAE's limited success does not preclude the use of climate scenarios and niche‐based SDMs when developing adaptation strategies, but suggests that such tools offer at best only a rough guide to identifying possible areas of future conservation value.

Comparison of indigenous and exogenous microbial populations during slurry phase biodegradation of long-term hydrocarbon-contaminated soil - Arturo Aburto-Medina; Eric M. Adetutu; Sam Aleer; John Weber; Sayali S. Patil; Petra J. Sheppard; Andrew S. Ball; Albert L. Juhasz (Biodegradation, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Paenibacillus polymyxa JB05-01-1 and its perspectives for food conservation and medical applications - Karim Naghmouchi; Lyn Paterson; Bob Forster; Tim McAllister; Sam Ohene-Adjei; Djamel Drider; Ron Teather; John Baah (Archives of Microbiology, 2011)

Local Participation in Natural Resource Monitoring: a Characterization of Approaches - FINN DANIELSEN; NEIL D. BURGESS; ANDREW BALMFORD; PAUL F. DONALD; MIKKEL FUNDER; JULIA P. G. JONES; PHILIP ALVIOLA; DANILO S. BALETE; TOM BLOMLEY; JUSTIN BRASHARES; BRIAN CHILD; MARTIN ENGHOFF; et al. (Conservation Biology, 2009)
The monitoring of trends in the status of species or habitats is routine in developed countries, where it is funded by the state or large nongovernmental organizations and often involves large numbers of skilled amateur volunteers. Far less monitoring of natural resources takes place in developing countries, where state agencies have small budgets, there are fewer skilled professionals or amateurs, and socioeconomic conditions prevent development of a culture of volunteerism. The resulting lack of knowledge about trends in species and habitats presents a serious challenge for detecting, understanding, and reversing declines in natural resource values. International environmental agreements require signatories undertake systematic monitoring of their natural resources, but no system exists to guide the development and expansion of monitoring schemes. To help develop such a protocol, we suggest a typology of monitoring categories, defined by their degree of local participation, ranging from no local involvement with monitoring undertaken by professional researchers to an entirely local effort with monitoring undertaken by local people. We assessed the strengths and weaknesses of each monitoring category and the potential of each to be sustainable in developed or developing countries. Locally based monitoring is particularly relevant in developing countries, where it can lead to rapid decisions to solve the key threats affecting natural resources, can empower local communities to better manage their resources, and can refine sustainable‐use strategies to improve local livelihoods. Nevertheless, we recognize that the accuracy and precision of the monitoring undertaken by local communities in different situations needs further study and field protocols need to be further developed to get the best from the unrealized potential of this approach. A challenge to conservation biologists is to identify and establish the monitoring system most relevant to a particular situation and to develop methods to integrate outputs from across the spectrum of monitoring schemes to produce wider indices of natural resources that capture the strengths of each.

Vegetation along hydrologic, edaphic, and geochemical gradients in a high-elevation poor fen in Canaan Valley, West Virginia - James S. Rentch; James T. Anderson; Sam Lamont; John Sencindiver; Robert Eli (Wetlands Ecology and Management, 2008)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Biogeochemistry and biodiversity of methane cycling in subsurface marine sediments (Skagerrak, Denmark) - R. John Parkes; Barry A. Cragg; Natasha Banning; Fiona Brock; Gordon Webster; John C. Fry; Ed Hornibrook; Richard D. Pancost; Sam Kelly; Nina Knab; Bo B. Jørgensen; Joachim Rinna; et al. (Environmental Microbiology, 2007)
Summary This biogeochemical, molecular genetic and lipid biomarker study of sediments (∼4 m cores) from the Skagerrak (Denmark) investigated methane cycling in a sediment with a clear sulfate‐methane‐transition zone (SMTZ) and where CH 4 supply was by diffusion, rather than by advection, as in more commonly studied seep sites. Sulfate reduction removed sulfate by 0.7 m and CH 4 accumulated below. 14 C‐radiotracer measurements demonstrated active H 2 /CO 2 and acetate methanogenesis and anaerobic oxidation of CH 4 (AOM). Maximum AOM rates occurred near the SMTZ (∼3 nmol cm −3 day −1 at 0.75 m) but also continued deeper, overall, at much lower rates. Maximum rates of H 2 /CO 2 and acetate methanogenesis occurred below the SMTZ but H 2 /CO 2 methanogenesis rates were × 10 those of acetate methanogenesis, and this was consistent with initial values of 13 C‐depleted CH 4 (δ 13 C c. −80‰). Areal AOM and methanogenic rates were similar (∼1.7 mmol m −2 day −1 ), hence, CH 4 flux is finely balanced. A 16S rRNA gene library from 1.39 m combined with methanogen (T‐RFLP), bacterial (16S rRNA DGGE) and lipid biomarker depth profiles showed the presence of populations similar to some seep sites: ANME‐2a (dominant), ANME‐3, Methanomicrobiales , Methanosaeta Archaea , with abundance changes with depth corresponding to changes in activities and sulfate‐reducing bacteria (SRB). Below the SMTZ to ∼1.7 m CH 4 became progressively more 13 C depleted (δ 13 C −82‰) indicating a zone of CH 4 recycling which was consistent with the presence of 13 C‐depleted archaeol (δ 13 C −55‰). Pore water acetate concentrations decreased in this zone (to ∼5 μM), suggesting that H 2 , not acetate, was an important CH 4 cycling intermediate. The potential biomarkers for AOM‐associated SRB, non‐isoprenoidal ether lipids, increased below the SMTZ but this distribution reflected 16S rRNA gene sequences for JS1 and OP8 bacteria rather than those of SRB. At this site peak rates of methane production and consumption are spatially separated and seem to be conducted by different archaeal groups. Also AOM is predominantly coupled to sulfate reduction, unlike recent reports from some seep and gassy sediment sites.

Chromatin dynamics and the evolution of alternate promoter states - Gordon L. Hager; Cem Elbi; Thomas A. Johnson; Ty Voss; Akhilesh K. Nagaich; R. Louis Schiltz; Yi Qiu; Sam John (Chromosome Research, 2006)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

A case of segmental paternal isodisomy of chromosome 14 - Karen J. Coveler; Sam P. Yang; Reid V. Sutton; Jay M. Milstein; Yuan-Qing Wu; Cami Bois; Linda S. Beischel; John P. Johnson; Lisa G. Shaffer (Human Genetics, 2002)

Age-Dependent Rates of Infection of Cassava Green Mites by a Fungal Pathogen in Brazil - Sam L. Elliot; John D. Mumford; Gilberto J. de Moraes; Maurice W. Sabelis (Experimental and Applied Acarology, 2002)

Importance of ambient saturation deficits in an epizootic of the fungus Neozygites floridana in cassava green mites (Mononychellus tanajoa) - Sam L. Elliot; Gilberto J. De Moraes; John D. Mumford (Experimental and Applied Acarology, 2002)

Commentary on: "Differential effects of amphetamine and neuroleptics on negative vs. positive symptoms in schizophrenia." Psychopharmacology (1980) 72:17-19 - Burt Angrist; John Rotrosen; Sam Gershon (Psychopharmacology, 2001)

Evaluation of Terrestrial and Streamside Salamander Monitoring Techniques at Shenandoah National Park - Robin E. Jung; Sam Droege; John R. Sauer; Ronald B. Landy (Environmental Monitoring and Assessment, 2000)

Immunization of rats reduces nicotine distribution to brain - Yoko Hieda; Dan E. Keyler; John T. VanDeVoort; R. Sam Niedbala; Donna E. Raphael; Cathy A. Ross; P. R. Pentel (Psychopharmacology, 1999)

The Pharmacokinetics and Electroencephalogram Response of Remifentanil Alone and in Combination with Esmolol in the Rat - Sam H. Haidar; J. Edward Moreton; Zhongming Liang; John R Hoke; Keith T. Muir; Natalie D. Eddington (Pharmaceutical Research, 1997)

A citywide breeding bird survey for Washington, D.C. - John Hadidian; John Sauer; Christopher Swarth; Paul Handly; Sam Droege; Carolyn Williams; Jane Huff; George Didden (Urban Ecosystems, 1997)

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)